Varicella-zoster virus prophylaxis with low-dose acyclovir in patients with multiple myeloma treated with bortezomib - Pour, Ludek; Adam, Zdenek; Buresova, Lucie; Krejci, Marta; Krivanova, Andrea; Sandecka, Viera; Zahradova, Lenka; Buchler, Tomas; Vorlicek, Jiri; Hajek, Roman (Clinical lymphoma & myeloma, 2009)
BACKGROUND: Varicella-zoster virus (VZV) reactivation is a common complication in patients with multiple myeloma (MM) treated with bortezomib, with an incidence rate of 10%-60%. The aim of our study was to analyze the effect of acyclovir prophylaxis in this patient population. PATIENTS AND METHODS: We studied 98 consecutive patients with relapsed MM treated with bortezomib. Bortezomib 1.3 mg/m2 was given on days 1, 4, 8, and 11 of a 21-day cycle. At first, patients did not receive any VZV prophylaxis, but because of the high incidence of VZV reactivation, VZV prophylaxis with acyclovir was implemented subsequently. RESULTS: A total of 11 patients treated with bortezomib did not have any VZV prophylaxis, and 4 of these 11 patients (36%) developed VZV reactivation in the form of herpes zoster. No VZV reactivations were observed in the 32 patients who received acyclovir 400 mg 3 times daily or the 55 patients who received acyclovir in a dose reduced to 400 mg once daily during bortezomib treatment. CONCLUSION: Varicellazoster virus reactivation is a common and serious adverse effect of bortezomib treatment. Acyclovir 400 mg once daily is sufficient to protect from VZV reactivation in patients with MM treated with bortezomib.
Keywords: Pyrazines; Humans; lidé středního věku; Virus Activation; Multiple Myeloma; Female; Aged; Herpes Zoster; Antineoplastic Agents; senioři; lidé; bortezomib; mnohočetný myelom; kyseliny boronové; ženské pohlaví; herpes zoster; Male; Middle Aged; antivirové látky; virus varicella zoster; Acyclovir; Bortezomib; acyklovir; pyraziny; Aged, 80 and over; Antiviral Agents; protinádorové látky; senioři nad 80 let; Boronic Acids; mužské pohlaví; prospektivní studie; Herpesvirus 3, Human; aktivace viru; Prospective Studies